Does Our Values Become Worsen? — A Study of the Effects of Fiscal Policies on Households’ Life in Sudan - Elryah, Yagoub (International Journal of Contemporary Economics and Administrative Sciences, 2015)
<span style="font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: 宋体; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; color: #222222; mso-font-kerning: 0pt;" lang="EN-US">As a result of the secession of South Sudan, Sudan has experienced the largest increases in the budget <span style="font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: 宋体; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; color: #222222; mso-font-kerning: 0pt;" lang="EN-US">deficit, shortages of hard currencies, highest inflation rates, and debt accumulation. In this paper, we attempt to extend and contribute to prior research on the impacts of fiscal policies on households’ life in Sudan. An online data from 1999 until 2013 were used to examine the effects of fiscal policy on households’ life in Sudan. To do this, the OLS and VECM estimation procedures were considered. Our results supported hypotheses that the households’ life has become more worsen than the situation in post-separation of South Sudan, which caused decline in the economy. The paper contributes to prior research within this field by addressing one of the challenges households in Sudan.<span style="mso-bidi-font-size: 10.5pt; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; color: #333333; background: white;" lang="EN-US">